The reliability and validity of a novel sport-specific balance test to differentiate performance levels in elite curling players - Pojskic, H.; McGawley, K.; Gustafsson, A.; Behm, D. G. (Journal of Sports Science & Medicine, 2020)
Balance as a skill and task-specific capacity is considered an es-sential physical quality in curling, required for executing effective stone delivery. However, no testing protocols have been devel-oped to test curling-specific balance in the delivery position.Thus, the primary aim of this study was to investigate the relia-bility, validity and usefulness of a newly-developed, curling-spe-cific balance test (CSBT) which involved the delivery position.The secondary aim was to examine the differences between elite and sub-elite curlers for core strength and flexibility, which have previously been identified as important qualities in curling and determinants of balance. Twenty curling players (13 females aged 19 ± 3.1 years; 7 males aged 19.6 ± 2.3 years) from five Swedish super-league curling clubs were divided into two groups accord-ing to playing level: elite and sub-elite. Variables included body mass, body height, body mass index, age, playing experience, training frequency, plank test, sit and reach test, standing single-leg balance test (SLBT) and CSBT. The CSBT was executed on a multiaxial tilting balance plate while mimicking the curling de-livery position (i.e., a deep lunge position with the front foot on the plate). The participants completed the CSBT on three separate occasions, with each test consisting of three, 20-s attempts. Both the relative and absolute reliability were good for the CSBT (ICC = 0.90; CV = 14.5%). The CSBT demonstrated good measure-ment usefulness, being sensitive to detect moderate changes that exceeded 0.5 times the test standard deviation. Construct validity of the CSBT was evidenced by the large discriminatory capacity to differentiate expertise level in curling players (t-test: 2.85, p < 0.01; large ES), irrespective of other physical capacities (e.g., flexibility and core strength). However, the elite and sub-elite players also differed in age, playing experience and training fre-quency. Content validity was confirmed by a weak correlation (r= 0.21; 95%CI: -0.26 to 0.60) between the CSBT and SLBT, which suggests that curling-specific and standing balance should be considered as independent and task-specific motor skills. Inconclusion, the CSBT can be used as a reliable, valid and useful tool for the assessment of curling-specific balance performance. In addition, longer and more extensive involvement in curling training contributed to superior specific balance in elite curlers.